Exogenous Hydrogen Peroxide Contributes to Heme Oxygenase-1 Delaying Programmed Cell Death in Isolated Aleurone Layers of Rice Subjected to Drought Stress in a cGMP-Dependent Manner - Wang, Guanghui; Xiao, Yu; Deng, Xiaojiang; Zhang, Heting; Li, Tingge; Chen, Huiping (Frontiers in Plant Science, 2018)
Hydrogen peroxide (H2O2) is a reactive oxygen species (ROS) that plays a dual role in plant cells. Here, we discovered that drought (20% polyethylene glycol-6000, PEG)-triggered decreases of HO-1 transcript expression and HO activity. However, exogenous H2O2 contributed towards the increase in HO-1 gene expression and activity of the enzyme under drought stress. Meanwhile, the HO-1 inducer hematin could mimic the effects of the H2O2 scavengers ascorbic acid (AsA) and dimethylthiourea (DMTU) and the H2O2 synthesis inhibitor diphenyleneiodonium (DPI) for scavenging or diminishing drought-induced endogenous H2O2. Conversely, the zinc protoporphyrin IX (ZnPPIX), an HO-1-specific inhibitor, reversed the effects of hematin. We further analyzed the endogenous H2O2 levels and HO-1 transcript expression levels of aleurone layers treated with AsA, DMTU, and DPI in the presence of exogenous H2O2 under drought stress, respectively. The results showed that in aleurone layers subjected to drought stress, when the endogenous H2O2 level was inhibited, the effect of exogenous H2O2 on the induction of HO-1 was enhanced. Furthermore, exogenous H2O2-activated HO-1 effectively enhanced amylase activity. Application of 8-bromoguanosine 3',5'-cyclic guanosine monophosphate (8-Br-cGMP) (the membrane permeable cGMP analog) promoted the effect of exogenous H2O2-delayed PCD of aleurone layers in response to drought stress. More importantly, HO-1 delayed the programmed cell death (PCD) of aleurone layers by cooperating with nitric oxide (NO), and the delayed effect of NO on PCD was achieved via mediation by cGMP under drought stress. In short, in rice aleurone layers, exogenous H2O2 (as a signaling molecule) triggered HO-1 and delayed PCD via cGMP which possibly induced amylase activity under drought stress. In contrast, as a toxic by-product of cellular metabolism, the drought-generated H2O2 promoted cell death.